FAKTOR INTERNAL BANK TERHADAP PENYALURAN KREDIT PADA BANK YANG GO PUBLIC DI INDONESIA - Ra. Berthy Widya Pusvitasari, 09.05.52.0064; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2013)
The purpose of this study was to find empirical evidence and analyze the effect of the Capital Adequacy Ratio, Return on Assets, Loan to Deposit Ratio, Loan and the amount of nonperfoming loans to the banking company in Indonesia Stock Exchange. The sample used in this study were 25 companies by using purposive sampling technique, sampling technique is based on the criteria, which is a company listed on the Stock Exchange and the companies that deliver financial year 2008 to 2011. Statistical tools used in this study using multiple linear regression models. From the results of tests performed on this study result that the variable CAR and significant negative effect on lending. While ROA variables have positive and significant impact on lending. For LDR and NPL variables have positive and significant impact on lending,Keywords: CAR, ROA, LDR, NPL